1941
DOI: 10.1152/ajplegacy.1941.132.2.489
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Blood Flow of the Liver

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

1942
1942
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…Therefore, it is suggested that normal hepatic blood flow in dogs is subject to wide spontaneous variations. Corrected blood flow measurement is in agreement with hepatic flow studies determined by the thermostromuhr and other methods (7,11,16,17).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, it is suggested that normal hepatic blood flow in dogs is subject to wide spontaneous variations. Corrected blood flow measurement is in agreement with hepatic flow studies determined by the thermostromuhr and other methods (7,11,16,17).…”
Section: Discussionsupporting
confidence: 80%
“…(Table V). Grindlay, Herrick, and Mann (17) reported hepatic blood flow in the dog to average 23 ml./Kg./min. without anesthesia and 22.6 ml./Kg./min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burton-Opitz (1911) and Barcroft & Shore (1912) estimated the mean contribution of this vessel to total hepatic flow to be between 30 and 34 % in the dog and cat. Thermostrohmuhr methods suggested even lower figures; Grindlay et al (1941) claim that the hepatic artery of the dog only carried 14-3 % of total liver blood. The findings of Ginsburg & Grayson (1954) using 'internal calorimetry', suggested that the coeliac axis contributed about 40 % of total hepatic blood.…”
Section: Contribution Of the Hepatic Artery To Liver Blood Flowmentioning
confidence: 96%
“…2.27 MeV, average 0.9 MeV) that have average tissue penetration of 2.5 mm and a maximum penetration of 11mm. Y-90 is produced in nuclear reactors by the neutron bombardment of Yttrium-89 [6]. Later, it is bound to resin or glass microspheres so that is can be used for treatment.…”
Section: Introductionmentioning
confidence: 99%